More is less: Effect of ICF-based early progressive mobilization on severe aneurysmal subarachnoid hemorrhage in the NICU - Yang, Xiaolong; Cao, Lei; Zhang, Tiantian; Qu, Xin; Chen, Wenjin; Cheng, Weitao; Qi, Meng; Wang, Na; Song, Weiqun; Wang, Ning (Frontiers in Neurology, 2022)
Introduction Aneurysmal subarachnoid hemorrhage (aSAH) is a type of stroke that occurs due to a ruptured intracranial aneurysm. Although advanced therapies have been applied to treat aSAH, patients still suffer from functional impairment leading to prolonged stays in the NICU. The effect of early progressive mobilization as an intervention implemented in the ICU setting for critically ill patients remains unclear. Methods This retrospective study evaluated ICF-based early progressive mobilization's validity, safety, and feasibility in severe aSAH patients. Sixty-eight patients with aSAH with Hunt-Hess grades III-IV were included. They were divided into two groups—progressive mobilization and passive movement. Patients in the progressive mobilization group received progressive ICF-based mobilization intervention, and those in the passive movement group received passive joint movement training. The incidence of pneumonia, duration of mechanical ventilation, length of NICU stay, and incidence of deep vein thrombosis were evaluated for validity. In contrast, the incidence of cerebral vasospasm, abnormally high ICP, and other safety events were assessed for safety. We also described the feasibility of the early mobilization initiation time and the rate of participation at each level for patients in the progressive mobilization group. Results The results showed that the incidence of pneumonia, duration of mechanical ventilation, and length of NICU stay were significantly lower among patients in the progressive mobilization group than in the passive movement group (P = 0.031, P = 0.004, P = 0.012), but the incidence of deep vein thrombosis did not significantly differ between the two groups. Regarding safety, patients in the progressive mobilization group had a lower incidence of cerebral vasospasm than those in the passive movement group. Considering the effect of an external ventricular drain on cerebral vasospasm (P = 0.015), we further analyzed those patients in the progressive mobilization group who had a lower incidence of cerebral vasospasm in patients who did not have an external ventricular drain (P = 0.011). Although we found 2 events of abnormally increased intracranial pressure in the progressive mobilization group, there was no abnormal decrease in cerebral perfusion pressure in the 2 events. In addition, among other safety events, there was no difference in the occurrence of adverse events between the two groups (P = 0.073), but the number of potential adverse events was higher in the progressive mobilization group (P = 0.001). Regarding feasibility, patients in the progressive mobilization group were commonly initiated 72 h after admission to the NICU, and 47.06% were in the third level of the mobilization protocol. Discussion We conclude that the ICF-based early progressive mobilization protocol is an effective and feasible intervention tool. For validity, more mobilization interventions might lead to less pneumonia, duration of mechanical ventilation and length of stay for patients with severe aSAH in the NICU, Moreover, it is necessary to pay attention over potential adverse events (especially line problems), although we did not find serious safety events.